The Competitive Role of Market Image in Maximizing Company Performance - Carp, Mihai; Chiriac, Irina; Afrasinei, Mihai-Bogdan; Georgescu, Iuliana Eugenia; Apostol, Ciprian (Transformations In Business & Economics, 2026)
Maximizing performance, though a challenging objective, remains a focal point for many leaders and organizations striving to continuously enhance operations and achieve desired outcomes. This paper aims to assess the influence of companies’ image on their commercial and stock performance. From an economic perspective, companies can enhance their sales or commercial performance (operating income/turnover), as well as their stock performance such as Price-to-Book Ratio (PBR) and return on shares. The study employs correlation analysis and multiple regression analysis on 200 companies listed on the Bucharest Stock Exchange, covering observations over a 9-year period from 2014 to 2022. We present suggestive evidence that factors such as media image, CEO gender, CEO age, and auditor reputation can impact sales growth, commercial profitability, and investor decisions. These findings carry significant implications for both economic theory and practice.